Peer Reviews in Scientific Journals: Recommendations from ODOVTOS - Reyes-Carmona, Jessie (2021)
The editorial process of a journal, specifically peer review, validates the scientific publication supported by the experience and knowledge of the reviewers. However, despite the fact that there are programs that instruct members of the scientific community in research, there are few training tools to participate in the arbitration of a manuscript. The purpose of this article was to present a guide with a series of recommendations on how a scientific article should be peer-reviewed. A synopsis of recommendations and criteria is presented and will be used by the reviewers of Odovtos-International Journal of Dental Sciences as a reference to support their work.